Aquatic macrophytes as indicators of water quality in subtropical shallow lakes, Southern Brazil - Pereira,Sabrina Amaral (2012)
AIMS: We evaluated the potential of aquatic macrophyte communities as bioindicators in six small shallow lakes. METHODS: The sampling was conducted monthly for one year, during which all macrophytes were surveyed, and the water temperature, dissolved oxygen, pH, conductivity, total alkalinity, chlorophyll-a, suspended matter, total nitrogen (Nt) and total phosphorus (Pt) were measured. RESULTS: In total, forty-three species were recorded, and there were significant differences in the species richness and limnological conditions among the lakes studied. A canonical correspondence analysis showed that the concentration of nutrients (Nt and Pt), chlorophyll-a, suspended matter, dissolved oxygen and pH were the most important predictors of the distribution of macrophytes. Some emergents were related to the high concentration of nutrients, chlorophyll-a, and suspended matter. Moreover, the most submersed species were associated with environments with low nutrient concentrations and the lowest values chlorophyll-a and suspended matter. In addition, some species submerged and floating were related to low values pH, alkalinity and dissolved oxygen. Limnological differences between lakes may be cited as the main causes of the observed heterogeneous distribution of macrophytes. CONCLUSIONS: These results indicate the importance of limnological characteristics of the different environments in the macrophyte community composition and the potential role of this community as a bioindicator in shallow lakes in southern Brazil.